MAKNA SIMBOLIK UPACARA MANGONGKAL HOLI BAGI MASYARAKAT SUKU BATAK TOBA PERANTAUAN (STUDI PADA MASYARAKAT BATAK TOBA DESA KASIKAN KABUPATEN KAMPAR) - Zecky Martin Putra; Ringgo Eldapi Yozana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Mangongkal Holi ceremony is one of the traditional rituals of the Batak Toba community that holds deep symbolic values and cultural meanings. This tradition involves the exhumation and relocation of the ancestors’ bones to a more proper place as a form of respect and honor for the ancestors. This study aims to determine the symbolic meaning of the Mangongkal Holi ceremony for the Batak Toba diaspora community in Kasikan Village, Kampar Regency. This research uses a qualitative method with an interpretive paradigm. Data were collected through non-participant observation, in-depth interviews, and documentation. The informants in this study were selected purposively, consisting of traditional leaders, pastors, and members of the Batak Toba community who were involved in the ceremony. The data analysis uses Herbert Blumer’s Symbolic Interactionism theory which emphasizes the meaning of situation, social interaction, and product meaning in the process of symbolic communication. The results of the study show that the symbolic meaning of the Mangongkal Holi ceremony for the Batak Toba diaspora community reflects respect for ancestors, strengthens clan identity, and reinforces kinship relationships within the Dalihan Na Tolu system. In addition, this ceremony also serves as a medium for preserving cultural values and as a symbol of family solidarity in the life of the Batak Toba community living outside their homeland. Keywords: Symbolic Meaning, Mangongkal Holi, Batak Toba, Diaspora